2022
DOI: 10.1021/acs.inorgchem.1c03531
|View full text |Cite
|
Sign up to set email alerts
|

Light-Driven Water Oxidation with Ligand-Engineered Prussian Blue Analogues

Abstract: The elucidation of the ideal coordination environment of a catalytic site has been at the heart of catalytic applications. Herein, we show that the water oxidation activities of catalytic cobalt sites in a Prussian blue (PB) structure could be tuned systematically by decorating its coordination sphere with a combination of cyanide and bidentate pyridyl groups.  K 0.1 [Co(bpy)] 2.9 [Fe(CN) 6 ] 2 ( [Cobpy–Fe] … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Post-catalytic PXRD analysis of [Co-Ni] revealed that the 2D structure is retained S7e and f, ESI †). 33,34 Similarly, the FTIR spectra of [Co-Ni] (Fig. 3e and Fig.…”
mentioning
confidence: 93%
“…Post-catalytic PXRD analysis of [Co-Ni] revealed that the 2D structure is retained S7e and f, ESI †). 33,34 Similarly, the FTIR spectra of [Co-Ni] (Fig. 3e and Fig.…”
mentioning
confidence: 93%
“…8 Cyanide-based coordination polymers Co−Fe PB have better water oxidation activity than the ones with a pentanuclear molecular structure. 6 Highly crystallized Na 2−x Fe-[Fe(CN) 6 ] y shows better stability as well as higher battery capacity than the low crystallized ones. 9 Besides tuning the PBAs through regulating the synthetic strategies, 6,9,10 many efforts have been devoted to study the effect of surfactants on the structures and sizes of PBA materials as well as on the catalytic activity of the PBA-derived materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…6 Highly crystallized Na 2−x Fe-[Fe(CN) 6 ] y shows better stability as well as higher battery capacity than the low crystallized ones. 9 Besides tuning the PBAs through regulating the synthetic strategies, 6,9,10 many efforts have been devoted to study the effect of surfactants on the structures and sizes of PBA materials as well as on the catalytic activity of the PBA-derived materials. 11−14 For example, it was found that the anionic surfactant sodium dodecyl sulfate (SDS) tends to adsorb on the (111) face of MnCo PB, which inhibits the decomposition of the (111) face and the growth of the (100) face, leading to the eventual formation of a hollow cube.…”
Section: ■ Introductionmentioning
confidence: 99%
See 2 more Smart Citations